The main causes of failure in removable dentures in Tripoli Libya - Albosefi, BDT, BDS, CAD, MSc* , Abdalah; al-nakow , BDT , Kawthar (Aljameai)
Abstract: The purpose of this study was to find out the main causes of failures in removable dentures, as well as the type and frequency of that failure in terms of several variables, in patients with removable dentures which had been supplied at private clinics. The study sample size were 50 patients with a mean age of (56.5years) distributed over nine private clinics, and the dentures were processed by three different dental laboratories. The medical conditions, complications and patient’s information was recorded. Also types of dentures and types of defects ware determined. After Statistical analyses was performed The most common complication was loss of retention (36.5%) followed by bad esthetic (24%), Where the most complaints was due to a manufacturing errors (52%). This study suggests that in most instances, removable denture patients present with complaints only when there is real design fault. Clinician must carefully evaluate the denture for faults in denture base, extension and horizontal and vertical jaw relationships المستخلص: الغرض من هذه الدراسة هو معرفة السبب الرئيسي لفشل اطقم الاسنان المتحركة ونوع هذا الفشل وتكراره من حيث العديد من المتغيرات في المرضى المستعملين لها، وقد بلغ حجم عينة الدراسة 50 مريضا بمتوسط عمر (56.5 ) سنة تم تقييمهم من قبل تسع عيادات خاصة، وتم تجهيز أطقم الأسنان من قبل ثلاثة مختبرات للأسنان. حيث تم تسجيل الحالات الطبية ، والعلاقة بين المضاعفات ومعلومات المريض ، وأنواع أطقم الأسنان ، وأنواع العيوب التي تم تحديدها. . بعد إجراء التحاليل الإحصائية كانت المضاعفات الأكثر شيوعا هي حركة الاطقم السنية المتحركة وعدم ثباتها في الفم 5.36% يليها المظهر السيئ 24٪ ، وقد تبين من النتائج ان معظم الشكاوى كانت بسبب أخطاء التصنيع 52٪. تشير هذه الدراسة إلى أنه في معظم الحالات ، لا يقدم مرضى أطقم الأسنان المتحركة شكاوى إلا عندما يكون هناك خطأ حقيقي في التصميم. ومن هنا يجب على الطبيب السريري تقييم طقم الأسنان بعناية بحثا عن اي أخطاء حتى يتسنى للمرضى استعمال هذا النوع من الاطقم دون اي مضاعفات او اضرار